Intergenerational instructional strategies and elderly preferences for digital applications: A Malaysian case study - Nahdatul Akma Ahmad; Muhammad Asri Mohd Ali; Tengku Shahrom Tengku Shahdan (PLoS ONE, 2025)
Introduction As Malaysia transitions into an ageing society, older adults increasingly face challenges in acquiring digital literacy, which impacts their ability to engage with essential online services, financial transactions, healthcare applications and communication platforms. The percentage of individuals aged 65 and above in Malaysia rose from 7.2% in 2022 to 7.4% in 2023, highlighting the growing needs for digital inclusion among this demographic. While internet adoption among older individuals is increasing, many still struggle due to psychological, cognitive, and physical barriers. Factors such as low self-efficacy, fear of complexity, and age-related physical limitations hinder their effective use of digital applications. Despite government initiatives such as MyDigital and the Malaysia Digital Economy Blueprint, gaps in digital literacy persist among older adults. Research suggests that intergenerational programs (IPs), where younger individuals assist older adults in learning digital skills, can bridge this gap. These programs promote collaborative learning, reduce social isolation, and foster meaningful intergenerational relationships. However, existing instructional strategies within IPs often fail to accommodate the specific learning needs and preferences of older adults, limiting their effectiveness. Addressing these instructional gaps is essential to ensuring older adults’ successful integration into the digital world. Aims This study aims to investigate the preferences of older adult individuals in Malaysia regarding digital applications and to propose effective intergenerational instructional strategies that enhance their digital learning experiences. Methods This qualitative study explores older adults’ preferences for digital applications and their experiences with intergenerational instructional strategies in Malaysia. A total of 26 older adults and 13 young instructors participated in digital applications workshops at two Pusat Aktiviti Warga Emas (PAWE) centres on August, 2024. Older adults were paired with young instructors in small groups to guide them in using digital applications through hands-on learning. Data collection involved semi-structured interviews before and after the sessions, as well as observations. Thematic analysis is used to analyse interview data, identifying key insights into improving digital learning for older adults in Malaysia. Results The study, conducted at two PAWE centres in Perak, Malaysia, explored intergenerational digital learning between 26 older adults (ages 59–82) and 13 young instructors (ages 20–24). Findings highlight the importance of structured instructional strategies, including interactive learning, direct instruction, and clear communication, to enhance digital literacy among older adults. Personalized learning approaches, small group discussions, and adapting content to individual needs improve engagement and comprehension. Smartphone familiarity plays a key role, with participants favouring WhatsApp and Facebook for communication. Older adults face challenges such as fear of complexity, physical limitations, and security concerns, while young instructors benefit from training to improve communication and instructional skills. The program fosters confidence, intergenerational bonding, and digital inclusion, demonstrating the value of tailored learning strategies in bridging the digital divide.